Selection for prolificacy in Finnsheep and in Norwegian sheep - Ådnøy, T. (Agricultural and Food Science, 1988)
Litter size (LS) at birth and other production traits were recorded for Finnsheep (F), Norwegian(N) breeds Dala (D), Steigar (St) and Spael (Sp), for N sheep crossed with 1/4 F and ½ F and for a group of sheep established by collecting offspring of highly prolific N(N+) ewes. The N breeds and the ¼ F group were part of the national breeding scheme. In the 1/2F and N+, selection was solely for LSB. The other groups were selected normally. There were 4263 lambings. In adults, there were no breed group differences in lambing-% (mean 94 %), but in 1-yr. olds there were differences: Sp 90 %, F and F-crosses 80—85 %, D 70 %, N+ 60 % and St 50 %. F-crosses had clearly the best LS’s (Fca. 3.0, 1/2F2.4, 1/4F2.0). Those of N+ decreased through the 5 years recorded from near 2.0 to 1.8 lambs. The other breed groups gave LS’s of 1.7—1.8. In the two groups selected for LS, no selection response was found. The reasons are not known. Although the pure F and ½ F gave lower weaning weights (34 and 38 kg at 150d.) than the other groups (41—45 kg), their weaned lamb yield per ewe was ca. 20 kg higher. Considering the poorer carcass quality observed in earlier experiments for these groups, the use of 1/4 F is recommended for Norwegian conditions. This breed group gave no reduction in weaning weight, but increased the LS by some 0.2 lambs.